Medical students: They’re not just little doctors! Impact of an online group-coaching program on medical student well-being: A randomized clinical trial - Adrienne Mann; Tyra Fainstad; Ivy Sullivan; Ethan M. Ritz; Jeffrey R. SooHoo; Hilit F. Mechaber; Ami Shah (PLoS ONE, 2025)
Introduction Physician burnout begins in medical school. Professional coaching can improve physician well-being, but generalizable evidence in medical students is lacking. We aim to evaluate a coaching program in a national sample of students. Materials and methods A randomized clinical trial assessing a four-month, web-based, group coaching program was conducted between September 1, 2023, and December 31, 2023, among medical students from seven institutions. The primary outcome was burnout measured using the Maslach Burnout Inventory. Secondary outcomes included impostor syndrome, moral injury, self-compassion, and flourishing. A linear mixed effect model analysis was performed on an intent-to-treat basis. Results Among the 390 participating students (mean [SD] age, 25.3 [2.38]), 197 were randomized to the intervention group. There were no significant post-coaching differences in burnout, moral injury or impostor syndrome between groups. After the coaching intervention, the intervention group had significantly greater self-compassion with an absolute difference of 3.00 points (SE = 1.29; 95% CI, 0.48 to 5.53 points; P = 0.021)), and significantly higher flourishing scores, with an absolute difference of 0.45 points (SE = 0.23; 95% CI, 0.01 to 0.90 points; P = 0.048) compared to the control. Conclusion Web-based group coaching did not have an impact on measures of distress in medical students, though did improve well-being outcomes including self-compassion and flourishing. Trial Registration: ClinicalTrials.gov Identifier: NCT05822375